Réponses

2014-03-30T10:09:35+02:00
Calculer la valeur de l'expression :

a) K = 2x'2 -6x + 1 , pour x = 5
K = 2 x 5² - 6 x 5 + 1
K = 2 x 25 - 30 + 1
K = 50 - 30 + 1
K = 51 - 30
K = 21

b) L = 10- 2x , pour x = -5
L = 10 - 2 x -5
L = 10 + 10
L = 20

Merci !
b) L = 10- 2x , pour x = -5
L = 10 - 2 x -5
L = 10 + 10
L = 20
2014-03-30T10:12:15+02:00
Salut :)

a) K = 2x² -6x + 1 ------> pour x = 5
K = 2 x 5² - 6 x 5 + 1
K = 2 x 25 - 30 + 1
K = 50 - 30 + 1
K = 21

b) L = 10- 2x -------> pour x = -5
L = 10 - 2 x (-5)
L = 10 + 10
L = 20

J'espère t'avoir aidé(e)! :)